The Influence of Product Quality and Price Perception on Purchasing Decisions of Mixue Ice Cream in Surabaya - Aldien Ramadhan; Zumrotul Fitriyah; Zawawi (Indonesian Journal of Business Analytics, 2023)
The proliferation of ice cream businesses in Indonesia has necessitated companies to engage in competitive rivalry, and Mixue ice cream is one such example. The perception of product quality and price assumes paramount significance, as it exerts a substantial influence on consumer decision-making in the context of purchasing. The objective of this research is to empirically investigate the impact of product quality and price perception variables on the purchasing decision of Mixue Ice Cream in Surabaya. The research methodology utilized in this study is quantitative research. The target population consists of consumers who have made purchases and consumed Mixue Ice Cream in East Surabaya. The data for this study will be collected through the utilization of a questionnaire. An ordinal scale with a Likert weighting of 1-5 will be employed to calculate the scoring of the questionnaire. The sampling method employed in this study is non-probability sampling, specifically utilizing purposive sampling technique to select respondents. The sample size comprises 100 respondents. The selected data analysis method to be employed in this research is descriptive analysis using Partial Least Squares (PLS). The findings of this research indicate a positive and significant influence of the product quality variable on purchasing decisions. The results of the second study reveal that the price perception variable also exerts a positive and significant impact on purchasing decisions.